„Z człowieka powstaje Bóg”. Terminologia przebóstwienia w pismach św. Grzegorza z Nyssy - Wyrąbkiewicz, Agnieszka (Vox Patrum, 2014)
Gregory of Nyssa presents the conception of human deification in an extraordinarily clear and concious way, using special verbs and characteristic expressions to emphasize the dynamism of the change of humanity into more divine. The Cappadocian Father, in order to maintain the apophatic nature of his doctrine, more and more often rejects the term of deification and describes it in his writings as participation of man in the divine nature, therefore the nominal term of deification never occurs in his literary works. However, the analysys of Gregory of Nyssa’s descriptions in which he refers to the terminology of deification has revealed a precisely chrystological and collective dimension of this process, which is possible to be taken up by man only owing to the energetic union connecting God and the world.